A Class of Transcendent Solution to Ernst System - Halilsoy, Mustafa (Lettere Al Nuovo Cimento, Societa Italiana di Fisica, 1985)
We present a method that generates a class of transcendent solutions to Ernst system in Einstein-Maxwell theory of general relativity.
The file in this item is the publisher version (published version) of the article.
Keywords: Ernst system; Einstein-Maxwell theory; general relativity